Principal's Leadership Style and Implications for Improving the Performance of PAI Teachers - Muhammad Akbar; Hafidz Hafidz; Abdul Hakim Abdurrahman Husein (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
School principals play a central role in school management and influence teacher performance, including Islamic Education (PAI) teachers who not only teach subject matter but also instill religious values in students. This study aims to examine the leadership style of school principals and its effect on improving the performance of PAI teachers at SMKN 1 Surakarta. The research approach used is descriptive qualitative, with informants consisting of school principals, PAI teachers, and vice principals in charge of curriculum, who were selected purposively. Data collection was conducted through interviews, documentation, and literature review, then analysed through reduction, presentation, and conclusion-drawing stages, and its validity was strengthened through source triangulation. The findings show that the principal combines transformational, democratic, situational, and participatory leadership styles. This approach encourages open communication, teacher involvement in decision-making, adjustment of directions according to teacher characteristics, and religious values education through school activities. The combination of these leadership styles has a positive impact on PAI teachers' performance, as seen in increased motivation, discipline, sense of responsibility, innovation in learning, and better teaching quality, while also strengthening the overall character building of students